2019
DOI: 10.1002/pat.4741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flame‐retardant ramie fiber on enhancing performance of the rigid polyurethane foams

Abstract: Ramie fiber (RF) with excellent tensile strength was treated by a flame retardant and obtained the modified RF (MRF) that is incombustible. Then, MRF was used to improve the performance of rigid polyurethane foams (RPUF). The mechanical properties of the composite were investigated by compressive strength test and shear stress test. The fire characteristics were studied using a cone calorimeter. And the thermal decomposition and flammable properties were further evaluated using thermogravimetric analysis and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The results presented in Table 3 indicate that depending on clove filler concentration, the porosity of PU foam composites decreases from 91% to 87% for samples PU-1 and PU-5, respectively. This phenomenon was well-described in previous studies and it is attributed to the poor interphase interaction between PU matrix and filler surface, which promotes cell collapsing of crowded cells leading to the formation of open cells [50][51][52].…”
Section: Cellular Structure Of Pu Composite Foamssupporting
confidence: 72%
“…The results presented in Table 3 indicate that depending on clove filler concentration, the porosity of PU foam composites decreases from 91% to 87% for samples PU-1 and PU-5, respectively. This phenomenon was well-described in previous studies and it is attributed to the poor interphase interaction between PU matrix and filler surface, which promotes cell collapsing of crowded cells leading to the formation of open cells [50][51][52].…”
Section: Cellular Structure Of Pu Composite Foamssupporting
confidence: 72%
“…Increased value of LOI is observed for PUR foams containing impregnated HS fillers—the LOI increases to 20.8 and 21.6%, for PUR_HS/SO and PUR_HS/TO, respectively. Chan et al [ 68 ] have reported similar results in the case of PUR foams enhanced with ramie fibers in the amount of 0.2–0.8 wt.%. It has been shown that the carbonization of the fibers during the combustion process results in the formation of pores, preventing the propagation of the flame through the PUR matrix and increasing the value of LOI.…”
Section: Resultsmentioning
confidence: 58%
“…When compared with the PUR_REF, the value of TSR decreases by ~7% for PUR_L, ~29% for PUR_L_K, and ~30% for PUR_L_HA. This suggests that incorporation of lavender fillers protects the PUR structure from further combustion and prevents the heat transfer [ 84 ] through the PUR matrix. Furthermore, the incorporation of lavender fillers can decrease the value of total heat release (THR).…”
Section: Resultsmentioning
confidence: 99%